Scenic art for the theatre : history, tools, and techniques - Crabtree, Susan, 1959- (Focal Press, 2005)
This new full color edition is significantly up-dated to new interviews with ""old masters"" and successful ""divas"" of the industry, up-dated safety tips, and additional insights into the business of scenic design. Expanded to include a new chapter dedicated to painting techniques, the book will now feature detailed step-by-step descriptions of common two-dimensional painting techniques. Wood graining, marble and stone, and brick painting are few examples of the new techniques to be covered